Light scattering of colloidal suspensions: formation and stability in bourbon whiskeys. Issue 2 (2nd May 2022) - Williams, Stuart J.; Islam, Sabina; Velev, Orlin D.
Abstract : The dilution of whiskey with water can lead to the formation of unwanted haze which is exacerbated at lower temperatures. This phenomenon is well known in the whiskey industry, and it is normal practice to use cold filtration to produce a clear product as well as improve product stability. However, to date, there has been no quantitative characterisation or understanding of the size and concentration of the colloidal particles as a function of whiskey dilution, temperature, and maturation. This report utilises light scattering techniques to characterise the formation of colloids in bourbon whiskeys of different aging periods. Higher water dilution decreased the size of the colloidal particulates and increased their stability. Aged samples (> 36 months) were found to be more stable, having a higher concentration of colloids at lower dilutions. This work demonstrates that dynamic light scattering can be useful for quality control in the spirits industry. © 2022 The Institute of Brewing & Distilling.